Effect of Additives on the Performance of Bio-lubricant Base Oil Produced from Colocynthis Seeds Oil - A. Yassin, Atif A.; E. Ahmed, Sulafa A.; A. Abdelrahman, Maha A.; Karama, Abdallah B. (Gezira Journal of Engineering and Applied Sciences, 2019)
Bio-lubricants are gaining popularity and acceptance globally due to their sustainable and environmentally friendly properties; being derived from feed stocks from vegetable oils. Where the main drawback of vegetable oils is; its poor oxidation stability and low temperature performance. This study aimed to study the effect of additives (Hitech 723) on the performance of bio-lubricant base oil produced from Colocynthis seeds oil. Hitech 723 additive package with different doses (0.3 and 0.6 g/100g oil), and pour point dispersant (PPD) additive with different doses (0.12 and 0.24g/100g oil) were added. Some physicochemical properties were measured before and after blending with additives. The addition of additives improved the kinematic viscosities, viscosity index, density and pour point of the base oil. The results of this study demonstrate that blending the bio-base oil from Colocynthis seeds and additives provides a suitable alternative to diesel lubricants base oil.                                              الملخص          مواد التشحيم الحيوية اكتسبت شعبية وقبول عالمي نسبة لخصائصها المستدامة والصديقة للبيئة. حيث ان للزيوت النباتية عيوب تتمثل في انخفاض معدل استقرار الأكسدة وانخفاض الأداء عند درجات الحرارة المنخفضة. تهدف هذه الدراسة لتحسين خواص الزيت الأساسي عن طريق مزجه مع بعض المحسنات, وقياس الخواص الفيزيوكيميائية قبل وبعد الاضافة. اضافة المحسنات حسنت اللزوجة الكينامتيكية، مؤشر اللزوجة، الكثافة ونقطة الانسكاب للزيت الأساسي. النتجة من هذه الدراسة اثبتت ان مزج الزيت المستخلص من بذور الحنظل مع حزم المحسنات يعطي بديلا مناسب  لمواد التشحيم البترولية.